Indonesian Consumers’ Purchase Behaviour of Green Innovative Product - Widodo, Arry; Abdul Wahid, Nabsiah (International Journal of Engineering and Technology, 2018)
This study aims to determine the reasons why Indonesian consumers buy innovative green products (Pertalite RON 90) using CAB attitude theory. This theory assumes that individual behavior (such as the decision to buy) is closely related to how they evaluate decisions of the cognitive, affective and conative aspects. This study was designed to be quantitative. The causal relationship between variables will be examined through questionnaires to be distributed to consumers of Indonesian motor vehicles using gasoline. The findings are expected to provide insight into whether ABC's theory of attitude, popular theory in consumer behavior literature is useful and applicable in explaining why consumers, especially Indonesian petrol consumers buy innovative green products (represented by Pertalite RON 90). From these findings, researchers and practitioners will be able to understand the importance of the cognitive, affective and conative components of the theory of consumer behavior and apply it accordingly. This study is important for the progress of CAB behavior theory through tripartite attitude structure model which consists of attitude stimulus through stimulus used to measure each component of cognitive, affective and conative behavior. The proposed model is intended to identify key concepts that shape attitudes that are useful for predicting outcomes to make accurate predictions using component attitude concepts: Cognitive, Influencing, and Conative (CAB), following tripartite behavioral models (Schiffman and Kanuk, 2004, Solomon, 2002; Breckler, 1984; Rosenberg and Hovland, 1960; Boulding, 1956).Â Â Â